Dutch and Portuguese in western Africa : empires, merchants and the Atlantic system, 1580-1674 - Silva, Filipa Ribeiro da, 1974- (Leiden ; Boston : Brill, 2011)
By looking at Dutch and Portuguese systems of settlement and trade in Western Africa, this book sheds new light on the formation of Dutch and Portuguese imperial frames, forms of commercial organisation and their role on the seventeenth-century-Atlantic.
Part I. Building Atlantic empires: the Dutch and the Portuguese models of settlement in western Africa: Building Institutions. Sending people: labour migration and forced labour. Shaping colonial societies -- Part II. Western Africa in the Dutch and the Portuguese Atlantic economies: the concept of "Atlantic system" and the study of interactions between states, companies and private merchants: Sailing in African waters: coastal areas and hinterland. Struggling for the Atlantic: the inter-continental trade. Doing business with western Africa: private investors, agency and commercial network -- Conclusion: new insights on Dutch-Portuguese rivalries in the Atlantic.
Includes bibliographical references (pages 335-384) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Africa, West -- Discovery and exploration -- Portuguese; Africa, West -- Discovery and exploration -- Dutch; Portuguese -- Africa, West -- History; Dutch -- Africa, West -- History; Netherlands -- Colonies -- Economic aspects -- Africa; Portugal -- Colonies -- Economic aspects -- Africa; Africa, West -- History -- To 1884.; Portugais -- Afrique occidentale -- Histoire; Néerlandais -- Afrique occidentale -- Histoire; Pays-Bas -- Colonies -- Aspect économique -- Afrique; Portugal -- Colonies -- Aspect économique -- Afrique; Afrique occidentale -- Histoire -- Jusqu'à 1884.; HISTORY -- Africa -- West; Discoveries in geography -- Dutch; Discoveries in geography -- Portuguese; Dutch; Economics; Netherlandish colonies; Portuguese; Portuguese colonies; Africa; West Africa; Kolonialisme; Nederlanders; Portugezen; Handel; West-Afrika.; To 1884; dissertations; Academic theses; History; Academic theses; Thèses et écrits académiques.